Is that you, Eleanor Sue? - Tusa, Tricia (Roaring Brook Press, 2018)
Saturdays are dress-up days when Eleanor Sue climbs out the window ... tiptoes over to the front door ... and rings the doorbell. When her mother answers, she doesn't see Eleanor Sue. She sees a cranky old neighbor. Or a hungry witch. Or a white-bearded wizard. Eleanor Sue is a master of disguise, but when her mother gets in on the act, along with Grandma, anything can happen.--